THE MODEL FOR IMPROVING BUSINESS PERFORMANCE USING MICROFINANCIAL INSTITUTIONS AND ENTREPRENEURSHIP COMPETENCIES - Erna Herlinawati; Riyandi Nur Sumawidjaja; Yoyo Sudaryo; Rama Chandra Jaya; Gurawan Dayona Ismail (Universitas Padjadjaran, 2023)
This paper will assess & present empirical evidence on the issue in order to better understand how Microfinance Institutions (MFIs) mediate entrepreneurial talents. The role of MFIs is evaluated based on their functions as a source of finance, facilitators for financial management, managerial management, and marketing management. Sales growth, profit growth, asset growth, employee growth, and market share growth are all ways to gauge a company’s performance. While entrepreneurial ability is assessed using technical, marketing, financial, and interpersonal abilities. The research approach is explanatory, with data collected through questionnaires and interviews. A sample of 150 SMEs sampled the population of 34,816 SMEs in West Java’s Greater Bandung region, Indonesia, using a proportionate random sampling approach. Structural Equation Modeling and a 5-point Likert scale were used to analyze the data collected (SEM). According to the findings, microfinance institutions can help businesses succeed by a small but significant amount. Business performance is positively and significantly impacted by entrepreneurial talents. The MFIS’s significance in influencing entrepreneurial skills expands in relation to corporate performance.